Cost benefit analysis of 20 mph zones in London. Issue 3 (30th August 2012) - Steinbach, Rebecca; Cairns, John; Grundy, Chris; Edwards, Phil
Abstract : Evidence suggests that 20 mph zones are an effective intervention to reduce casualties from road traffic crashes in urban areas. This analysis compares the costs of construction of the 20 mph zone intervention in high and low casualty areas in London to the value of casualties avoided over 5 and 10 year time horizons. Probabilistic sensitivity analyses were conducted to quantify uncertainty in the results associated with model parameters. Results indicate a net present value (NPV) of £18 947 (90% credible limits −£75 252 to £82 021 2005 prices) after 5 years and £67 306 (£−29 157 to £137 890) after 10 years when 20 mph zones are implemented in areas with one or more casualty per kilometre of road. Simulations from our model suggest that the 'threshold of casualties' where NPVs become positive using a 10 year time horizon is 0.7 casualties per kilometre.